Fenologia foliar de três espécies de Byrsonima e suas variações fisiológicas em resposta à sazonalidade hídrica no Cerrado - Pereira, Barbara (2018)
Abiotic stresses are limiting to plant development, and can generate physiological responses ranging from changes in cellular metabolism, photosynthetic yield, and accumulation of carbohydrates to changes in morphology and in phenological patterns. In this work, physiological variations between three sympatric species: Bysrsonima intermedia, Byrsonima coccolobifolia and Byrsonima verbascifolia occurring at Cerrado area of the Brazil southeast were evaluated. The three species present morphologically distinct leaves and different foliar habits. Specific leaf mass (SLM), leaf relative water content (RWC), leaf phenology, leaf carbohydrate content, osmotic potential (Ψs) and chloroplastidic pigments, and maximum quantum yields were evaluated. Byrsonima intermedia and B. coccolobifolia are semi-deciduous, while B. verbascifolia was the only one classified as evergreen. No differences were observed between SLM values, neither between months nor between species. The values of RWC and maximum quantum yield were lower in June reflecting rainfall. The water content was different between the months and B. intermedia presented lower values in December. The high RWC in August (dry season month) would be an indicator of osmotic adjustment, related to the increase of total soluble sugars contents and osmotic potential (Ψs). Byrsonima intermedia and B. coccolobifolia presented RWC values higher than B. verbascifolia. Total chlorophyll and carotenoids contents were higher in June, indicative of a photoprotection mechanism and dissipation of excess energy in the photosynthetic system during stressfull periods. No large reductions in photosynthetic yield values were observed between dry season months, indicating that all the three species are well adapted to prevailing environmental conditions. The development of phenophases seems to be related to the water supply throughout the year.